2021
DOI: 10.1007/s10453-021-09718-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and size distribution in the airborne indoor microbial concentration of residential houses in Delhi and its impact on health

Abstract: Exposure of microbial agents in the air of indoor dwellings is associated with effects on respiratory and general health. The current study was conducted in the urban area of Delhi Metropolis for the seasonal quantitative assessment of viable microbial indoor air quality. Bioaerosol measurement was conducted by using Anderson six stage impactor with cut-off diameters of 7.0, 4.7, 3.3, 2.1, 1.1, and 0.65 µm) throughout the all the seasons (April 2019 to March 2020). Meteorological parameters such as temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Staphylococcus, Micrococcus, and Streptococcus were the most dominant bacterial genera in indoor than outdoors in the current study and previous studies [28,31,35]. A high abundance of Cladosporium in indoors indicate that outdoor conditions significantly affect the indoor fungal concentration.…”
Section: Plos Onesupporting
confidence: 72%
See 2 more Smart Citations
“…Staphylococcus, Micrococcus, and Streptococcus were the most dominant bacterial genera in indoor than outdoors in the current study and previous studies [28,31,35]. A high abundance of Cladosporium in indoors indicate that outdoor conditions significantly affect the indoor fungal concentration.…”
Section: Plos Onesupporting
confidence: 72%
“…Few studies have been conducted in Delhi to measure biological pollution at various locations, with the majority of the studies focusing on educational institutes, libraries, dumping sites, and so on [27,28,37,[44][45][46]. In addition, the houses of patients suffering from asthma/ allergies reported (110,091) and (107,070) fungal colonies per cubic meter area in indoor and outdoor areas, respectively reported by [47].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted on infants with asthma, Gent et al (2002) reported that the higher Penicillium concentrations were linked to a higher likelihood of wheezing and chronic cough. Seasonal changes in the environment are known to determine important variations in outdoor airborne fungal communities (Larsen, 1981;Kumar et al, 2021;Núñez et al, 2021;Yuan et al, 2022). We found a significant difference in fungal concentration in the analyzed environments in Tianjin, with the highest level recorded in spring and the lowest in winter.…”
Section: Discussionmentioning
confidence: 72%
“…The concentration and exposure duration may cause a serious range of allergic diseases related to the skin, eyes, ears, gastrointestinal tract and respiratory system (Faridi et al, 2016;Sandeep et al, 2020). Such incidences are more prominent in industrial areas than residential and commercial areas (Kumar et al,2021). For instance, the inhalation of industrial and agricultural specks of dust is considered as the principal cause of respiratory allergy in occupational areas (Dutkiewicz, 2011).…”
Section: Introductionmentioning
confidence: 99%